PERANANAN KULIAH KERJA NYATA PENGABDIAN KEPADA MASYARAKAT MANDIRI BERBASIS DARING SEKOLAH TINGGI ILMU HUKUM LUBUK SIKAPING DINAGARI-NAGARI DALAM MEMBANTU PEMERINTAH MENGATASI COVID 19 TAHUN 2020 - Nur Asmah; Hardimen Hardimen (Ensiklopedia of Journal, 2022)
At the beginning of 2020, the whole world was shocked by the COVID-19 outbreak that started in China, Wuhan City. This pandemic has caused thousands of people to be infected with the COVID-19 virus and others have died. In Indonesia, the government has given advice to all levels of Indonesian society to be alert to the Covid-19 pandemic. The Indonesian government has made recommendations for Large-Scale Social Restrictions (PSBB), Lockdown, Social distancing etc. The aim is to raise public awareness which is the main key to breaking the chain of the Covid-19 outbreak. President Joko Widodo said that universities must function as water towers, not ivory towers. This means that all research and innovations produced by universities must be useful for the community. This was conveyed by Jokowi when he inaugurated the Sultan Ageng Tirtayasa (Untirta) Sindang Sari University Campus, Serang City, Banten, Thursday (4/3/2021). "Universities are not located in ivory towers, but must function as water towers where the results of research and innovations produced by the campus must be directly felt by the community.